2021
DOI: 10.1136/bmjsem-2020-000876
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in the expression of core-clock genes correlate with resting muscle properties and predict fluctuations in exercise performance across the day

Abstract: ObjectivesIn this study, we investigated daily fluctuations in molecular (gene expression) and physiological (biomechanical muscle properties) features in human peripheral cells and their correlation with exercise performance.Methods21 healthy participants (13 men and 8 women) took part in three test series: for the molecular analysis, 15 participants provided hair, blood or saliva time-course sampling for the rhythmicity analysis of core-clock gene expression via RT-PCR. For the exercise tests, 16 participant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 77 publications
2
46
0
Order By: Relevance
“…It is also important to notice that each patient (or healthy individuals) and each cancer are unique. Accordingly, different cell lines, patients or healthy individuals [62] have specific clock phenotypes, and this requires personalization of treatment. Thus, any clinical application requires that our model is fitted to the individual patient, or to groups of patients with similar clock molecular profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to notice that each patient (or healthy individuals) and each cancer are unique. Accordingly, different cell lines, patients or healthy individuals [62] have specific clock phenotypes, and this requires personalization of treatment. Thus, any clinical application requires that our model is fitted to the individual patient, or to groups of patients with similar clock molecular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Several patient-friendly methods for measuring clock-gene expression in saliva or blood samples have been recently validated in the clinics (see [12] for a review). Furthermore, strong oscillations, clearly above noise level, are expected in core-clock gene expression, which facilitates the characterisation of their circadian profiles and reduces the number of needed time points to do so [62] . In addition, a newly available statistical algorithm offers to derive clock gene mRNA circadian rhythms from a single-time-point measurement of 10 clock genes [68] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basti et al . [ 33 ] reported that the exercise performance correlates with daily fluctuation in core-clock genes and peaks in the late-afternoon (15:00–18:00) hours irrespective of gender, but it is always better to keep individual chronotype in perspective for achieving better results of the exercise. An acute bout, participant characteristics and sample size limit the application of our study results to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that there is intramuscular temperature dependency on muscle force generation [67,147,194], and the core body temperat- [53,194] and athletic performance in general [495,644].…”
Section: F Thermal and Circadian Measurementsmentioning
confidence: 99%